The Influence of Air Flow Rates and Voltage on the Plasma Emission Spectra and the Concentrations of Nitrogen Oxides Produced by Gliding Arc Discharge Plasma - Liutauras Marcinauskas; Rolandas Uscila; Mindaugas Aikas (Applied Sciences)
In this work, gliding arc discharge (GAD) was used to produce air plasma and investigate the influence of the discharge parameters on the composition of the air plasma, vibrational temperatures, and the production of NOx. It was demonstrated that the main particles obtained in the GAD air plasma were N2*, N2+, N+, NOγ, and O. It was observed that the reduction in the discharge frequency increased the intensity of the excited nitrogen molecules lines and reduced the nitric oxide (NO) and nitrogen dioxide (NO2) gas concentrations. The increase in the output voltage prolonged the duration of arc discharge and enhanced the intensities of the emission lines of the N2+, O, and NOγ species and the concentrations of NO and NO2 gasses. It was shown that the increase in the air flow rate from 6.7 L/min to 15.6 L/min decreased the concentration of the produced NO gas by 24%. Additionally, the line intensities of all main species in air plasma were enhanced. Studies have shown that the NO and NO2 gas concentrations (selectivity of NO and NO2) can be controlled by varying the air flow, output voltage, and discharge frequency. The highest NOx concentration of 2380 ppm was produced at 250 V, when the direct air flow was 11.2 L/min.